ADULT LANGERHANS CELL HISTIOCYTOSIS WITH MULTISYSTEM INVOLVEMENT - Ng, Wei Wei; Wahab, Norasyikin A. (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Langerhans cell histiocytosis (LCH) is a rare, heterogenous disease with a wide range of manifestations, from unifocal lesions to multisystem involvement. Commonly affected sites include the bone, lungs, pituitary gland, liver, bone marrow, and skin. We report a case of adult-onset LCH presenting with unifocal bony lesions and hypophysitis. CASE A 34-year-old female presented in June 2022 with polyuria and polydipsia for four months. Serum sodium was 148 mmol/L, serum osmolality 309 mOsmol/kg and urine osmolality 62 mOsmol/kg. Water deprivation test confirmed central diabetes insipidus. In September 2022, she complained of amenorrhea for three months but denied headaches, visual disturbances, galactorrhea or significant weight changes. Menstrual cycles were previously regular. She had two children, with her last childbirth two years prior. Anterior pituitary function was consistent with central hypogonadism (LH: 2.1 IU/L, FSH: 5.3 IU/L). Autoimmune screening and tumour markers were negative. Magnetic resonance imaging of the pituitary revealed a thickened pituitary stalk and the absence of bright spot in the posterior pituitary. No biopsy was performed. Hence, she was treated for hypophysitis and given desmopressin as well as estradiol. Six months later, she developed left shoulder pain. Radiographs revealed a 3.0 x 4.6 x 5.4 cm lytic lesion in the left scapula. She underwent curettage and excision, and histopathological examination confirmed LCH with neoplastic cells expressing CD1a and S100. The patient did not consent for chemotherapy. One year after diagnosis, she developed central hypothyroidism (free T4: 8.2 nmol/L, TSH: 0.12 mU/L), and was started on levothyroxine. During her latest follow-up, she was asymptomatic, with no new lesions on imaging. Cortisol axis remains intact. CONCLUSION Adult-onset LCH is rare and biopsy remains the gold standard for diagnosis. This case highlights the diagnostic challenge of distinguishing LCH from other causes of hypophysitis. A comprehensive systemic evaluation is crucial for accurate diagnosis and assessment of disease extent.